The averaged lagrangian of solitons of Bose-Einstein condensation - Zhumaev, M.R.; Sharipov, M.Z.; Mirzhonova, N.N. (Publishing House of the KarSU named after E.A.Buketov, 2018)
The effect of the fluctuation interaction of atoms forming a condensate on solitons of the Bose- Einstein condensation is considered. A short derivation of the Gross-Pitaevsky equation is given. The averaged Lagrangian of solitons of the Bose-Einstein condensation is determined. The obtained results give an opportunity to investigate the solitons dynamics under the action of various perturbations.
Keywords: Bose-Einstein condensate; Gross-Pitaevskii equation; averaged Lagrangian